99mTc-Unithiol-Komplex, ein neues Radiopharmazeutikum für die Nierenszintigraphie. - Darte, L.; Oginski, M.; Persson, R. B. R. (Nuklearmedizin - NuclearMedicine, 1979)
Labelling of 2, 3-dimercaptopropane sodiumsulphonate (Unithiol) with 99mTc resulted in essentially three components in the GCS pofile: the top zone, a low-molecular Complex A and a high-molecular Complex B. In the presence of tin metal a fourth component, Complex C, could be distinguished. Complex A was relatively independent of pH, the proportion of Complex B increased with increasing pH. Methods were developed for preparing, with over 80% labelling efficiency, either Complex A or Complex B, each having high stability in the preparation vials and in human blood.